2014
DOI: 10.1186/1471-2458-14-1224
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the health of transgender and other gender minority populations: Validity of natal sex and gender identity survey items in a U.S. national cohort of young adults

Abstract: BackgroundA barrier to monitoring the health of gender minority (transgender) populations is the lack of brief, validated tools with which to identify participants in surveillance systems.MethodsWe used the Growing Up Today Study (GUTS), a prospective cohort study of U.S. young adults (mean age = 20.7 years in 2005), to assess the validity of self-report measures and implement a two-step method to measure gender minority status (step 1: assigned sex at birth, step 2: current gender identity). A mixed-methods s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 30 publications
2
122
2
4
Order By: Relevance
“…Additional studies are needed using mixed methods to formally validate the survey items to measure natal sex/gender identity status using a two-step method. Cognitive testing of the modified survey items (Reisner et al, 2013; Sudman, Bradburn, & Schwarz, 1996) is recommended in different languages, and geographic contexts, using diverse samples. This would ideally include confirming accurate classification of transgender cases (i.e., that people checking cross-sex, transgender, or other gender are being classified correctly as transgender).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional studies are needed using mixed methods to formally validate the survey items to measure natal sex/gender identity status using a two-step method. Cognitive testing of the modified survey items (Reisner et al, 2013; Sudman, Bradburn, & Schwarz, 1996) is recommended in different languages, and geographic contexts, using diverse samples. This would ideally include confirming accurate classification of transgender cases (i.e., that people checking cross-sex, transgender, or other gender are being classified correctly as transgender).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a two-step approach offers a method of measuring transgender identity in the U.S. (Sausa et al, 2009; Tate et al, 2013). We view the two-step cross-classification procedure as a method to categorize the construct of natal sex/gender identity status in health research (Reisner et al, 2013a). The current study extended previous work by offering conceptual precision of the construct being measured, bringing the two-step method into a global context, and offering Spanish and Portuguese translations of two survey items for health research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender was assessed using a two-step method asking two items: (1) assigned sex at birth (female, male) and (2) current gender identity (man, woman, female-to-male (FTM)/trans man, male-to-female (MTF)/trans woman, genderqueer, gender variant, gender-nonconforming, other; Reisner et al, 2014b, 2014c). The two items were cross-tabulated to categorize participants as female-to-male (FTM) spectrum or male-to-female (MTF) spectrum according to their natal sex and current gender identity.…”
Section: Methodsmentioning
confidence: 99%